E-GOVERNMENT BASED ON CLOUD ENVIRONMENT IN INDONESIA - Mubarik Ahmad; Zainal A. Hasibuan (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2012)
E-government is a concept that is believed to improve government services. The revolution of technology nowadays may lead to cloud computing in e-government where services as its core. From literatures, cloud environment offers manybenefits than traditional infrastructure. Therefore, Indonesia as developing country with unique geographical background should be looked at this alternative. From worldwide ranking, e-government in Indonesia is considered less than satisfactory. Implementation e-government tends to ineffective and inefficient. This is because of problems that are found from traditional infrastructure such as lack of competency for human resources in ICT, lack of integration,inefficient investment of infrastructure in regions, etc. Cloud environment is expected to overcome those problems withservice on demand concept on centralized infrastructure. This paper proposes initial architecture for implementing egovernment based on cloud computing in Indonesia.